2012
DOI: 10.1002/rsa.20471
|View full text |Cite
|
Sign up to set email alerts
|

Maximum edge‐cuts in cubic graphs with large girth and in random cubic graphs

Abstract: We show that for every cubic graph G with sufficiently large girth there exists a probability distribution on edge-cuts in G such that each edge is in a randomly chosen cut with probability at least 0.88672. This implies that G contains an edge-cut of size at least 1.33008n, where n is the number of vertices of G, and has fractional cut covering number at most 1.127752. The lower bound on the size of maximum edge-cut also applies to random cubic graphs. Specifically, a random n-vertex cubic graph a.a.s. contai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Also evolving from the early version of our method in [23], Kardoš, Král and Volec [30] found strong lower bounds on the size of maximum cuts in cubic graphs with large girth, which improved on earlier bounds of Zýka [51], and the first author [24] found lower bounds on the largest induced forest in regular graphs with large girth.…”
Section: Related Work and Examples Of Improved Boundsmentioning
confidence: 71%
See 2 more Smart Citations
“…Also evolving from the early version of our method in [23], Kardoš, Král and Volec [30] found strong lower bounds on the size of maximum cuts in cubic graphs with large girth, which improved on earlier bounds of Zýka [51], and the first author [24] found lower bounds on the largest induced forest in regular graphs with large girth.…”
Section: Related Work and Examples Of Improved Boundsmentioning
confidence: 71%
“…Strangely perhaps, relaxing the independence condition does not produce any easy significant improvement. For maximum cuts in cubic graphs, we derive analytic lower bounds, based on differential equations, such that the bounds obtained in [30] can be interpreted as long recurrences for computing numerical approximations of our analytic result.…”
Section: Related Work and Examples Of Improved Boundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The case where d is small and the girth (length of a shortest cycle) is large has also been considered: for 3-regular graphs, Kardoš, Král' and Volec [17] showed that when the girth is at least 637789, there exists a randomized distributed algorithm that outputs a cut of average size at least 0.88672m in at most 318894 rounds (the important value here is the size of the cut). This was improved by Lyons [20], who proved a lower bound of 0.89m for cubic graphs of girth at least 655.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this is the expected size of a uniformly random cut. Moreover, though there are certain classes of graphs for which the max-cut is significantly larger (see, for example, [22]), the max-cut of an m-edge graph is typically quite close to m/2. As such, much of the focus has been on maximising the excess of a cut, defined to be its size minus m/2.…”
Section: Introductionmentioning
confidence: 99%